Perbedaan Prestasi Belajar Mata Pelajaran Keagamaan Antara Santriwati Program Reguler dan Program Intensif Kelas V TMI Puteri Al-Amien Prenduan - Yusuf, Nurul Husna (Anterior Jurnal, 2015)
Departing from different educational backgrounds, the female students of the graduate SD/MI (regular program) and female students graduated from junior high school/MT (intensive program), then is there any difference in learning achievement are achieved mainly in religious subjects at grade students V. To the authors conduct research in TMI Princess Al-Amien Prenduan. As the population is female students of class V 181 students consisting of 67 students from the regular program and 114 students intensive program. The samples using random sampling techniques by means of a lottery that consists of 50 students from the regular program and 50 students of the intensive program. While the value of learning achievement is taken from the report cards of students who become documents in TMI institutions Princess Al-Amien Perenduan. Thus Ho is accepted, meaning that there is no difference in learning achievement in the subjects of religion among female students and female students regular program intensive program class V. The learning achievement santriwati regular program represented sample showed a mean value = 6.36, which means that the learning achievement of female students in the regular program of religious subjects including good enough category. While learning achievement santriwati intensive program showed a mean value = 5.94 categorized enough. From the above results, it can be the authors mentioned that there was no significant difference between students' learning achievement and regular program students intensive courses in religious subjects.